The Brothers Grimm and the Making of German Nationalism - Norberg, Jakob (Humanities, 2022)
In this first comprehensive English-language portrait of the Brothers Grimm as political thinkers and actors, Jakob Norberg shows how history's two most famous folklorists aspired to define national identity, delineate national borders, and even counsel regimes. This title is also available as Open Access on Cambridge Core.